Pengembangan Buku Saku Berbasis Mind Mapping Materi Bentuk Keberagaman di Indonesia Untuk Peningkatan Hasil Belajar PPKn Sekolah Dasar - Karmin Toro; Slamet Utomo; Suad Suad (Jurnal Prakarsa Paedagogia, 2021)
This research aims to (1) analyze the necessary development, (2) develop, and (3) analyze the reliability of the mind mapping based pocketbook with the materials about the diversity in Indonesia to enhance the fourth graders’ civics learning outcomes in Rara Mendut cluster, Pati . This Research and Development used Borg and Gall model. The data were obtained from the interview, questionnaire, and attitude scale techniques. The results of the research are: First, the Pocketbook development is needed to improve the learning outcome by considering the characteristics of Civics materials and the developed learners’ cognitions at the concrete-operational stage. Secondly, the Pocketbook was successfully developed through 7 stages. Third, the Pocketbook was reliable with a very reliable criterion. N-Gain test on the trial run product obtained a percentage of 0.39. It meant there was an improvement result between the pretest and posttest with a moderate category.